1995
DOI: 10.1007/bf00223936
|View full text |Cite
|
Sign up to set email alerts
|

Somatic hybrids between Brassica juncea (L). Czern. and Diplotaxis harra (Forsk.) Boiss and the generation of backcross progenies

Abstract: An attempt to transfer genes from droughttolerant Diplotaxis harra, a wild relative of Brassica species, to an elite oil-yielding cultivar, B-85, of mustard (Brassica juncea) was made through protoplast fusion, as the two plant systems are sexually incompatible. By following the standard protocol for PEG-mediated protoplast fusion followed by high pH, high Ca(++), DMSO treatment and appropriate cell-culture technique, 16 presumptive somatic hybrid plants could be regenerated. Chromosomal analysis of four such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…These intergeneric hybrids were characterized by hybrid morphological features and contained more than 2n = 58 chromosomes. Further studies of the progenies were not reported (Klimaszewsla & Keller, 1988;Begum et al, 1995).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…These intergeneric hybrids were characterized by hybrid morphological features and contained more than 2n = 58 chromosomes. Further studies of the progenies were not reported (Klimaszewsla & Keller, 1988;Begum et al, 1995).…”
Section: Introductionmentioning
confidence: 83%
“…Plants consisted of 2n = over 58 chromosomes (Begum et al, 1995). The hybrid plant obtained by protoplast fusion between B. napus and D. harra, exhibited hybrid features and consisted of 2n = over 60 chromosomes (Klimaszewsla & Keller, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of total genomes of the two parents, especially nuclear ones, in a hybrid has two obvious disadvantages, introduction of too much exotic genetic material accompanying the expected gene(s) and genetic imbalance leading to somatic incompatibility. These limitations could cause either abnormal growth and development of the somatic hybrids or regeneration of hybrids with low fertility (Wang et al, 1989;Sherraf et al, 1994;Spangenberg et al, 1994;Begum et al, 1995;Kisaka et al, 1998;Hu et al, 2002b;Wang et al, 2003). For example, the somatic hybrids between Arabidopsis thaliana and Brassica napus, Lycium barbarum and tobacco (Nicotiana tabacum) did not develop roots (Bauer-Weston et al, 1993;Liu et al, 1995b).…”
Section: Symmetric Versus Asymmetric Fusion and Treatments In Asymmetmentioning
confidence: 94%
“…Isoenzymes of esterase (Bauer-Weston et al, 1993), peroxidase (Begum et al, 1995;Xia et al, 1998;Xu et al, 2003), phosphoglucose isomerase (Fahleson et al, 1994b), phosphoglucomutase (Ochatt et al, 1989), glutamate aspartic aminotransferase (Jain et al, 1988), phosphatase (Yamaguchi and Shiga, 1993), menadione reductase (Klimaszewska and Keller, 1988) and leucine aminopeptidase (Hansen and Earle, 1997) have been used for confirming hybrid nature of regenerants from intergeneric fusions. Subunits of Fraction-I protein, RUBPCase, have been used to characterize somatic hybrids based on isoelectric focusing (Shepard et al, 1983).…”
Section: Isoenzyme and Fraction-i Proteinmentioning
confidence: 98%
“…Resistance genes were transferred against bacterial (Hansen and Earle 1995;Laferriere et al 1999), fungal (Hansen and Earle 1997) and virus diseases (Austin et al 1985;Gibson et al 1988), or even nematodes (Lelivelt et al 1993). Somatic transfer of cytoplasmic male sterility (Kyozuka et al 1989;Akagi et al 1995) has been achieved and improvement of drought (Begum et al 1995) or cold tolerance (Louzanda et al 1993) was also attempted via somatic hybridization.…”
Section: Introductionmentioning
confidence: 99%